2012
DOI: 10.3390/ijerph9082694
|View full text |Cite
|
Sign up to set email alerts
|

Non-Genomic Effects of Xenoestrogen Mixtures

Abstract: Xenoestrogens (XEs) are chemicals derived from a variety of natural and anthropogenic sources that can interfere with endogenous estrogens by either mimicking or blocking their responses via non-genomic and/or genomic signaling mechanisms. Disruption of estrogens’ actions through the less-studied non-genomic pathway can alter such functional end points as cell proliferation, peptide hormone release, catecholamine transport, and apoptosis, among others. Studies of potentially adverse effects due to mixtures and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 143 publications
(222 reference statements)
2
39
0
Order By: Relevance
“…Numerous studies have investigated the influence of BPA on human health, especially reproductive health, since the ovary is an active organ that is susceptible to harmful environmental exposure. Previous studies revealed that BPA can suppress ovarian follicle growth by causing perturbations in estrogen metabolism (Mohri and Yoshida, 2005;Richter et al, 2007;Vinas et al, 2012) or meiotic division (Eichenlaub-Ritter et al, 2008;Hunt et al, 2003;Suzuki et al, 2002). Recent evidence suggests that BPA perturbs various ovarian functions such as folliculogenesis and follicle formation in vitro (Susiarjo et al, 2007;Hunt et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have investigated the influence of BPA on human health, especially reproductive health, since the ovary is an active organ that is susceptible to harmful environmental exposure. Previous studies revealed that BPA can suppress ovarian follicle growth by causing perturbations in estrogen metabolism (Mohri and Yoshida, 2005;Richter et al, 2007;Vinas et al, 2012) or meiotic division (Eichenlaub-Ritter et al, 2008;Hunt et al, 2003;Suzuki et al, 2002). Recent evidence suggests that BPA perturbs various ovarian functions such as folliculogenesis and follicle formation in vitro (Susiarjo et al, 2007;Hunt et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…And these problems increase when more "metabolic" signaling pathways, like thyroid, PPAR, retinoids, and others, in which the so-called non-genomic effects (effects on hormone metabolism, transport or degradation, neuroendocrine control, etc.) may easily shadow the more "classic", receptor-binding linked effects [57,[77][78][79][80].…”
Section: A Practical Approach: Predictive Endocrine Disruptionmentioning
confidence: 99%
“…Based upon numerous previous studies, xenoestrogens, also called "environmental estrogens or hormones" or "Endocrine Disrupting Compounds (EDC)", are considered as serious environmental hazards that have hormone disruptive effects on human and wildlife health [5,6]. Studies have found that fetuses and young children exposed to BPA are at risk for secondary sexual developmental changes, brain and behavior changes and immune disorders [7].…”
Section: Environmental Estrogen-biphenol a (Bpa)mentioning
confidence: 99%